Protecting children from secondhand smoke: a mixed-methods feasibility study of a novel smoke-free home intervention - Marsh, John; McNeill, Ann; Lewis, Sarah; Coleman, Tim; Bains, Manpreet; Larwood, Alexandra; Purdy, Jacqueline; Jones, Laura L. (Biomed Central, 2016)
Background: Globally, 40 % of children under 14 years are regularly exposed to secondhand smoke (SHS), typically in their homes. There is limited evidence of the effectiveness of interventions to reduce children’s SHS exposure,and so the aim of this study was to test the feasibility and acceptability of a novel intervention to help parents and carers (caregivers) to reduce their children’s exposure to SHS at home.